One-pot Synthesis of Unsymmetrical Diaryliodonium Tetrafluoroborate Salts Bearing an Isoxazole Moiety from Aryl Boronic Acids - A.F. Abdul Manan, M; B. Cordes, D; M.Z. Slawin, A; O’Hagan, D (International Journal of Engineering and Technology, 2019)
Hypervalent iodine compounds exhibit attractive features of low cost, mild and selective reagents in organic synthesis. These reagents serve as environmentally benign alternatives to toxic heavy-metal based oxidants and expensive organometallic catalysts. The practical and simple synthesis of unsymmetrical diaryl iodonium tetrafluoroborate salts is described. This synthetic method has allowed the production of isoxazole tetrafluoroborate salts from readily available aryl boronic acids without an extra anion exchange step in acceptable yields of 45% and 50%. Â